Yahudi Helenis untuk Terjemahan Kata Yunani Ἑλληνιστὰι dalam Alkitab Indonesia: Sebuah Studi Semantik - Yonky Karman (Veritas : Jurnal Teologi dan Pelayanan, 2022)
The meaning of the neologism Ἑλληνιστὰι in the New Testament (Acts 6:1; 9:29; 11:20), although only three times, is not as simple as one might think. The Indonesian Bible (TB, BIMK) defines its first two usages as linguistic differences (“Greek-speaking Jews”). The third usage is not even clear whether it is the category of descent (“Greeks”) or religious (“non-Jewish people”). There is a tendency for Ἑλληνιστὰι to be translated non-uniformly, but there is also a uniformity. In the context of this word study, the first step is to determine Ἕλληνες as the root and origin of Ἑλληνιστὰι. Since the semantic meaning of Ἕλληνες includes Greeks by descent and Greeks culturally, the second step is to examine the consistency of the differentiation of Graeci and gentiles in the Vulgate for both Greekishness. The fact that Ἑλληνιστὰι translations are so varied makes the final step necessary, namely to reinterpret the word in its context. As a result, neologism is needed for Indonesian vocabulary: “Helenis” (or Hellenist) for cultural Ἕλληνες and “Yahudi Helenis” (or Hellenized Jews) for Ἑλληνιστὰι.